Physician Report Cards and Implementing Standards of Practice Are Both Significantly Associated With Improved Screening Colonoscopy Quality. (August 2015) - Keswani, Rajesh N; Yadlapati, Rena; Gleason, Kristine M; Ciolino, Jody D; Manka, Michael; O'Leary, Kevin J; Barnard, Cynthia; Pandolfino, John E
Abstract : OBJECTIVES: Adenoma‐detection rates (ADRs) are associated with decreased interval colorectal cancer (CRC) rates and CRC mortality; quality improvement strategies focus on improving physician ADRs. The objective of this study was to examine the sequential effect of physician report cards and implementing institutional standards of practice (SOP) on ADRs. METHODS: Colonoscopy metrics were prospectively evaluated at a single academic medical center over a 23‐month period (November 2012 to October 2014). ADRs were evaluated over three time periods—Period 1: Before initial report card distribution or SOP (November 2012 to March 2013); Period 2: After individualized report card distribution detailing physician and institutional ADRs (April 2013 to March 2014); Period 3: After second report card and SOP implementation (April 2014 to October 2014). The SOP required physicians to have a minimum 5‐min withdrawal time in normal colonoscopies (WT) and an ADR minimum of 20%; those who did not meet benchmarks would require further training or endoscopy block time alterations. Only endoscopists averaging >15 colonoscopies/month were included in this analysis. RESULTS: Twenty endoscopists met the inclusion criteria, performing 12, 894 screening colonoscopies over the 23‐month period. Following report card distribution, physician ADRs increased by 3% ( P <0.001). SOP implementation resulted in a further significant increase in mean physician ADR of 8% ( P <0.0001). Overall, mean ADR increased by 11% from Period 1 to Period 3 ( P <0.0001). All physicians met the minimum 20% ADR benchmark during Period 3. Although ADRs significantly correlated with WT overall ( r =0.45; 95% CI 0.01, 0.75; P =0.04), mean WT did not significantly increase from Period 1 to Period 3. CONCLUSIONS: Our data suggest that distributing colonoscopy quality report cards resulted in a significant ADR improvement. Further, we report evidence that implementing SOP significantly improved ADRs beyond report card distribution and resulted in all endoscopists meeting minimum benchmarks. This suggests that report cards and SOPs may have an additive effect in improving colonoscopy quality, and their implementation in endoscopy labs should be encouraged.